ARTIK-52 induces replication-dependent DNA damage and p53 activation exclusively in cells of prostate and breast cancer origin. Issue 3 (1st February 2016) - Fleyshman, Daria; Cheney, Peter; Ströse, Anda; Mudambi, Shaila; Safina, Alfiya; Commane, Mairead; Purmal, Andrei; Morgan, Kelsey; Wang, Nicholas J.; Gray, Joe; Spellman, Paul T.; Issaeva, Natalia; et al.
ABSTRACT: The realization, that the androgen receptor (AR) is essential for prostate cancer (PC) even after relapse following androgen deprivation therapy motivated the search for novel types of AR inhibitors. We proposed that targeting AR expression versus its function would work in cells having either wild type or mutant AR as well as be independent of androgen synthesis pathways. Previously, using a phenotypic screen in androgen-independent PC cells we identified a small molecule inhibitor of AR, ARTIK-52. Treatment with ARTIK-52 caused the loss of AR protein and death of AR-positive, but not AR-negative, PC cells. Here we present data that ARTIK-52 induces degradation of AR mRNA through a mechanism that we were unable to establish. However, we found that ARTIK-52 is toxic to breast cancer (BC) cells expressing AR, although they were not sensitive to AR knockdown, suggesting an AR-independent mechanism of toxicity. Using different approaches we detected that ARTIK-52 induces replication-dependent double strand DNA breaks exclusively in cancer cells of prostate and breast origin, while not causing DNA damage, or any toxicity, in normal cells, as well as in non-PC and non-BC tumor cells, independent of their proliferation status. This amazing specificity, combined with such a basic mechanism of toxicity, makes ARTIK-52 a potentially useful tool to discover novel attractive targets for the treatment of BC and PC. Thus, phenotypic screening allowed us to identify a compound, whose properties cannot be predicted based on existing knowledge and moreover, uncover a barely known link between AR and DNA damage response in PC and BC epithelial cells.